Stability over time of scores on psychiatric rating scales, questionnaires and cognitive tests in healthy controls. Issue 2 (2nd March 2022) - Stahl, Katharina; Adorjan, Kristina; Anderson-Schmidt, Heike; Budde, Monika; Comes, Ashley L.; Gade, Katrin; Heilbronner, Maria; Kalman, Janos L.; Klöhn-Saghatolislam, Farahnaz; Oraki Kohshour, Mojtaba; Papiol, Sergi; Reich-Erkelenz, Daniela; et al.
Abstract : Background: Case-only longitudinal studies are common in psychiatry. Further, it is assumed that psychiatric ratings and questionnaire results of healthy controls stay stable over foreseeable time ranges. For cognitive tests, improvements over time are expected, but data for more than two administrations are scarce. Aims: We comprehensively investigated the longitudinal course for trends over time in cognitive and symptom measurements for severe mental disorders. Assessments included the Trail Making Tests, verbal Digit Span tests, Global Assessment of Functioning, Inventory of Depressive Symptomatology, the Positive and Negative Syndrome Scale, and the Young Mania Rating Scale, among others. Method: Using the data of control individuals ( n = 326) from the PsyCourse study who had up to four assessments over 18 months, we modelled the course using linear mixed models or logistic regression. The slopes or odds ratios were estimated and adjusted for age and gender. We also assessed the robustness of these results using a longitudinal non-parametric test in a sensitivity analysis. Results: Small effects were detected for most cognitive tests, indicating a performance improvement over time ( P < 0.05). However, for most of the symptom rating scales and questionnaires, no effects were detected, in line with our initial hypothesis. Conclusions: The slightly but consistently improved performance in the cognitive tests speaks of a test-unspecific positive trend, while psychiatric ratings and questionnaire results remain stable over the observed period. These detectable improvements need to be considered when interpreting longitudinal courses. We therefore recommend recruiting control participants if cognitive tests are administered.